Zur Pluralität der ökonomischen Politikberatung in Deutschland - Stephan Pühringer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2021)
Dieser Beitrag setzt sich mit der Frage des Pluralismus in der ökonomischen Politikberatung. Anhand von drei empirischen Beispielen wird gezeigt, dass sowohl was politisch-ideologische Orientierung als auch das Geschlechterverhältnis betrifft, ökonomische Politikberatung in Deutschland lange Zeit wenig plural war, in jüngster Zeit allerdings einige Trends zur Pluralisierung auszumachen sind. – – This paper deals with the question of pluralism in economic policy advise. Based on three empirical examples it is shown that economic policy advise in Germany was not very pluralistic in terms of gender ratio and political-ideological orientation of economists. Recent developments however, point to a slight trend of pluralization in this field.
Keywords: 330; Pluralismus; ökonomische Politikberatung; Ordoliberalismus; Wirkmächtigkeitökonomischen Wissens; Soziologie der Ökonomie; pluralism; economic policy advise; ordoliberalism; performativity of economics; social studies of economics